Sistem Informasi Keluhan Pelanggan Pada Perusahaan Daerah Air Minum (PDAM) Kabupaten Lombok Tengah - Rohana Rohana; Khairul Imtihan (Jurnal Manajemen Informatika dan Sistem Informasi, 2018)
The development of information technology increasingly faster, one of the advantages obtained is the easier people in communicating, sending information, or get information. This needs improved performance in terms of effectiveness and efficiency of service providers (Sukmana, 2014). Perusahaan Daerah Air Minum (PDAM) Lombok Tengah in the service of customer complaints whether it be leak pipe complaints, meter replacement, inappropriate water usage and water is often jammed, Officer will check customer data on customer information then record customer's complaint and save on book complaint customer. After conducting data collection on the complaint, the officer in the subscriber hubungan langganan (HUBLANG) will make the warrant to be submitted to the transmisi dan distribusi (TRANSDIT) to make improvements made by the maintenance department, because the complaint process is still recorded in the customer complaint book allowing the complaint data is lost or scattered so it can hinder the process of repair or maintenance, so that required a system that can process and store customer complaints data. The method of designing customer complaint information system at Perusahaan Daerah Air Minum (PDAM) Lombok Tengah uses SDLC (Systems Development Life Cycle) method with planning, analysis, design, implementation and testing phase. In the planning phase, data collecting using obsevation method, interview and literature study are used in the analysis phase using SWOT method (strengths, weaknesses, opportunities, threats), at design stage, the system design will be proposed using DFD (Data Flow Digram) starting from diagram Context of Customer Complaints Information System and DFD Level 1 Customer Complaints Information System, followed by table design, design of ERD (entity relationship diagram), design of menu structure and design of system interfaces, in the implementation phase of the system made system in accordance with the design phase using php programming language with the mysql database while in the testing phase using the method of balck box system, the results of the design will be easier for customers in the process of complaint submission without having to come again to the PDAM Kabupaten Lombok Tengah and can facilitate the subscriber hubungan langganan (HUBLANG) in recording customer data that conduct customer complaints process